Bile accelerates carcinogenic processes in pancreatic ductal adenocarcinoma cells through the overexpression of MUC4 - Gál Eleonóra; Veréb Zoltán; Kemény Lajos; Rakk Dávid; Szekeres András; Becskeházi Eszter; Tiszlavicz László; Takács Tamás; Czakó László; Hegyi Péter; Venglovecz Viktória (2020)
Pancreatic cancer (PC) is one of the leading causes of mortality rate globally and is usually associated with obstructive jaundice (OJ). Up to date, there is no clear consensus on whether biliary decompression should be performed prior to surgery and how high levels of serum bile affects the outcome of PC. Therefore, our study aims were to characterise the effect of bile acids (BAs) on carcinogenic processes using pancreatic ductal adenocarcinoma (PDAC) cell lines and to investigate the underlying mechanisms. Liquid chromatography-mass spectrometry was used to determine the serum concentrations of BAs. The effects of BAs on tumour progression were investigated using different assays. Mucin expressions were studied in normal and PDAC cell lines and in human samples at gene and protein levels and results were validated with gene silencing. The levels of BAs were significantly higher in the PDAC + OJ group compared to the healthy control. Treating PDAC cells with different BAs or with human serum obtained from PDAC + OJ patients enhanced the rate of proliferation, migration, adhesion, colony forming, and the expression of MUC4. In PDAC + OJ patients, MUC4 expression was higher and the 4-year survival rate was lower compare to PDAC patients. Silencing of MUC4 decreased BAs-induced carcinogenic processes in PDAC cells. Our results show that BAs promote carcinogenic process in PDAC cells, in which the increased expression of MUC4 plays an important role. Based on these results, we assume that in PC patients, where the disease is associated with OJ, the early treatment of biliary obstruction improves life expectancy.